2015
DOI: 10.1007/s11277-015-2587-8
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Transceiver Scheme for SC-FDMA Systems Based on Discrete Wavelet Transform and Discrete Cosine Transform

Abstract: In this paper, the discrete cosine transform (DCT) is utilized for single carrier frequency division multiple access (SC-FDMA) transmission. Firstly, an improved DCTbased SC-FDMA (DCT SC-FDMA) system is introduced. Then, the paper presents a new transceiver architecture design for the uplink SC-FDMA system that implements a cosine basis function or a complex exponential Fourier basis function. The proposed architecture uses the discrete wavelet transform and a hybrid companding and clipping method for peak-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…This work is the further advancement of our recent research work [10]. Implementing the DCT‐SCFDMA system proposed in [1], the efficaciousness of our proposed PAPR dilution process is ascertained in this work. In addition, a comparative analysis with aforementioned system incorporating pulse shaping process only has portrayed the significant advantage of our scheme in terms of BER performance.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This work is the further advancement of our recent research work [10]. Implementing the DCT‐SCFDMA system proposed in [1], the efficaciousness of our proposed PAPR dilution process is ascertained in this work. In addition, a comparative analysis with aforementioned system incorporating pulse shaping process only has portrayed the significant advantage of our scheme in terms of BER performance.…”
Section: Introductionmentioning
confidence: 82%
“…In wireless communication technology, single carrier frequency division multiple access (SCFDMA) technique has drawn much attention for being implemented in the uplink communication due to its lower peak‐to‐average power ratio (PAPR). A novel method using discrete cosine transform (DCT) as basis function in SCFDMA system is proposed by Al‐Kamal et al [1]. Impressive energy compaction characteristic is found in DCT rather than in discrete Fourier transform (DFT) process which makes the system more flexible to scale down the effect of inter‐symbol interference (ISI) significantly [2].…”
Section: Introductionmentioning
confidence: 99%
“…At a certain BER=10 -4 , it observed that, the performance gain is better for the proposed DCT-SCFDMA system over the DCT-SCFDMA system modeled in [16] when the QPSK modulation scheme has been adopted for interleaved subcarrier allocation. The desired symbol suffers less interference coming from neighboring symbols in proposed DCT-SCFDMA system.…”
Section: Ber Performancementioning
confidence: 97%
“…The universal pulse that satisfies Eqs. (3) and (4) is the conventional raised-cosine (RC) filter, which has the following spectral magnitude [16]-…”
Section: Fig 1 : Impulse Response Of the Rc Filtermentioning
confidence: 99%
“…For different values of IBO, we can note a reduction of about 2 dB by applying the proposed method, compared to the original signal. This is mainly the effect of the DCT method, known for its good frequency compaction and a good spectral efficiency [35]. Combined with shaping technique, it allows significant PAPR reduction while help maintaining the spectrum in the standard specification.…”
Section: Constellations Inmentioning
confidence: 99%